Curcumin β‐D‐glucuronide exhibits anti–tumor effects on oxaliplatin‐resistant colon cancer with less toxicity in vivo. Issue 5 (7th April 2020) - Ozawa‐Umeta, Hitomi; Kishimoto, Atsuhiro; Imaizumi, Atsushi; Hashimoto, Tadashi; Asakura, Tadashi; Kakeya, Hideaki; Kanai, Masashi
Abstract: The NF‐kappa B (NF‐κB) pathway plays a pivotal role in tumor progression and chemoresistance, and its inhibition has been shown to suppress tumor growth in a variety of preclinical models. Recently, we succeeded in synthesizing a water‐soluble injectable type of curcumin β‐D‐glucuronide (CMG), which is converted into a free‐form of curcumin by β‐glucuronidase in vivo. Herein, we aimed to clarify the efficacy, safety and pharmacokinetics of CMG in a xenograft mouse model. First, we confirmed that the presence of KRAS/TP53 mutations significantly increased the IC50 of oxaliplatin (L‐OHP) and NF‐κB activity in HCT116 cells in vitro. Then, we tested the efficacy of CMG in an HCT116 colon cancer xenograft mice model. CMG demonstrated superior anticancer effects compared to L‐OHP in an L‐OHP‐resistant xenograft model. With regard to safety, significant bodyweight loss, severe myelosuppression and AST/ALT elevation were observed in L‐OHP‐treated mice, whereas none of these toxicity was noted in CMG‐treated mice. The combination of CMG and L‐OHP exhibited additive effects in these xenograft models without increasing toxicity. Pharmacokinetic analysis revealed that high levels of free‐form curcumin were maintained in the tumor tissue after 48 hours following CMG administration, but it was not detected in other major organs, such as the heart, liver and spleen. Immunohistochemistry revealed reduced NF‐κB activity in the tumor tissue extracted from CMG‐treated mice compared with that from control mice. These results indicated that CMG could be a promising anticancer prodrug for treating colon cancer with minimal toxicity. Abstract : Curcumin β‐D‐glucuronide exhibits anticancer effects in an oxaliplatin‐resistant colon cancer xenograft model with minimal toxicity.